Using Social Support Matter in the Association of Post-Traumatic Cognitions and Perceived Social Support? Comparison of Female Survivors of Intimate Partner Violence With and Without a History of Child Abuse - Dodson, Thomas S. (Journal of interpersonal violence, 2021)
The association between high levels of post-traumatic stress disorder (PTSD) symptoms and low levels of perceived social support is well-documented in the trauma literature; research on processes that may underlie this association is less common. The current study examined negative attitudes about using social support as a potential link between negative post-traumatic cognitions about the world and self, one aspect of PTSD, and perceived social support in two groups of female survivors of intimate partner violence: those who had a history of child abuse (n = 153; IPV/CA+) and those who did not (n = 96; IPV/CA−). Negative attitudes about using social support were found to be an important link between negative post-traumatic cognitions and social support for both groups. IPV survivors with a history of child abuse had higher levels of negative post-traumatic cognitions about the world (d = .32) and self (d = .33), greater negative attitudes about using social support (d = .35), and lower perceived social support from family (d = .48), compared with IPV survivors without a history of child abuse. These results support the relevance of negative attitudes about using social support as one important factor in the relationship between PTSD symptoms and social support in interpersonal trauma survivors and highlight the impact that negative attitudes about using social support can have on the trauma survivor’s functioning.